2018
DOI: 10.1080/13696998.2018.1440401
|View full text |Cite
|
Sign up to set email alerts
|

A best–worst scaling in Colombian patients to rank the characteristics of HIV/AIDS treatment

Abstract: This study suggests that treatment characteristics regarding efficacy and prolongation of life are particularly important for patients in Colombia. Further investigation on how patients make trade-offs between these important characteristics and incorporating this information in clinical and policy decision-making would be needed to improve adherence with HIV/AIDS medication.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 15 publications
2
17
0
Order By: Relevance
“…short-term (physical activity) and longterm (life expectancy)) the most important attributes. These findings are in line with a previous best-worst scaling that was conducted in Colombia and revealed that efficacy and prolonging life expectancy were the most important attributes 22 . Our study, using a DCE, offers the advantage to assess the trade-offs between the most important attributes.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…short-term (physical activity) and longterm (life expectancy)) the most important attributes. These findings are in line with a previous best-worst scaling that was conducted in Colombia and revealed that efficacy and prolonging life expectancy were the most important attributes 22 . Our study, using a DCE, offers the advantage to assess the trade-offs between the most important attributes.…”
Section: Discussionsupporting
confidence: 91%
“…First, a literature review in PubMed was conducted to examine which attributes were used in previous DCEs on patients' preferences in HIV treatment [16][17][18][19][20][21]30 . In addition, a previous best-worst scaling study of Hendriks et al 22 , which identified the most important treatment characteristics of HIV patients in Colombia, was used as the main basis for the attributes of the present study. Then, two independent researchers (AG and ES) blindly conducted a first selection.…”
Section: Attributes and Levelsmentioning
confidence: 99%
See 2 more Smart Citations
“…We previously conducted a bestworst scaling to elicit the most important HIV/AIDS treatment characteristics in Colombia. This study revealed that Colombian patients mostly valued drug efficacy, maximum prolongation of life and long duration of efficacy 13 .…”
Section: Introductionmentioning
confidence: 86%